Management of Allogeneic Stem Cell Transplantation for High-Risk AML following SARS-CoV-2 Associated Pancytopenia with Marked Bone Marrow Biopsy Alterations. (22nd January 2021) - Kaparou, Maria; Rudzki, Zbigniew; Giles, Hannah; Murthy, Vidhya; Srinath, Swathy; Lloyd, Rebecca; Ahmed, Maria Zahid; Salhan, Beena; Chauhan, Saleena; Kishore, Bhuvan; Lovell, Richard; Horgan, Claire; et al.
Abstract : The present study describes a patient aged 70 with very high-risk AML who successfully received a nonmyeloablative matched unrelated donor allograft shortly following SARS-CoV-2 infection, which manifested with mild cough, interstitial abnormalities on chest CT, and pancytopenia with profound bone marrow biopsy histological alterations. In parallel, our study provides bone marrow biopsy data in a series of contemporary patients with serious haematological diseases who had a bone marrow biopsy performed within two weeks of PCR confirmation of SARS-CoV-2 infection. This study is notable because there are no published data describing the bone marrow biopsy changes observed in patients with haematological malignancies and SARS-CoV-2 infection. Finally, it is suggested that nonmyeloablative hematopoietic stem cell transplantation for very high-risk haematological malignancies can be successfully performed following recovery from SARS-CoV-2 infection.